Treatment with benznidazole and pentoxifylline regulates microRNA transcriptomic profile in a murine model of Chagas chronic cardiomyopathy. - Priscila Silva Grijó Farani; Beatriz Iandra da Silva Ferreira; Khodeza Begum; Glaucia Vilar-Pereira; Isabela Resende Pereira; Edith A Fernández-Figueroa; Roberto Alejandro Cardenas-Ovando; Igor C Almeida; Sourav Roy; Joseli Lannes-Vieira; Otacilio Cruz Moreira (Public Library of Science (PLoS), 2023)
Chronic Chagas cardiomyopathy (CCC) is one of the leading causes of morbidity and mortality due to cardiovascular disorders in endemic areas of Chagas disease (CD), a neglected tropical illness caused by the protozoan parasite Trypanosoma cruzi. CCC is characterized by parasite persistence and inflammatory response in the heart tissue, which occur parallel to microRNA (miRNA) alterations. Here, we investigated the miRNA transcriptome profiling in the cardiac tissue of chronically T. cruzi-infected mice treated with a suboptimal dose of benznidazole (Bz), the immunomodulator pentoxifylline alone (PTX), or the combination of both (Bz+PTX), following the CCC onset. At 150 days post-infection, Bz, PTX, and Bz+PTX treatment regimens improved electrocardiographic alterations, reducing the percentage of mice afflicted by sinus arrhythmia and second-degree atrioventricular block (AVB2) when compared with the vehicle-treated animals. miRNA Transcriptome profiling revealed considerable changes in the differential expression of miRNAs in the Bz and Bz+PTX treatment groups compared with the control (infected, vehicle-treated) group. The latter showed pathways related to organismal abnormalities, cellular development, skeletal muscle development, cardiac enlargement, and fibrosis, likely associated with CCC. Bz-Treated mice exhibited 68 differentially expressed miRNAs related to signaling pathways like cell cycle, cell death and survival, tissue morphology, and connective tissue function. Finally, the Bz+PTX-treated group revealed 58 differentially expressed miRNAs associated with key signaling pathways related to cellular growth and proliferation, tissue development, cardiac fibrosis, damage, and necrosis/cell death. The T. cruzi-induced upregulation of miR-146b-5p, previously shown in acutely infected mice and in vitro T. cruzi-infected cardiomyocytes, was reversed upon Bz and Bz+PTX treatment regimens when further experimentally validated. Our results further our understanding of molecular pathways related to CCC progression and evaluation of treatment response. Moreover, the differentially expressed miRNAs may serve as drug targets, associated molecular therapy, or biomarkers of treatment outcomes.